VIRTUAL CERTAINTY IN VIDEO GAMES: ITS INFLUENCE ON THE IMMERSIVE EXPERIENCE AND THE DEVELOPMENT OF NARRATIVES - Ariso, José María (ENDOXA, 2025)
Drawing inspiration from Wittgenstein’s notion of “certainty,” I argue that in many video games one can distinguish between everyday certainties and certainties characteristic of each video game. To refer to this kind of certainties, in this paper I introduce the notion of “virtual certainty” and present its distinguishing features. Then I explain why the fact of sharing virtual certainties constitutes a re-ontologization or immersion in a world-picture – i.e. a set of certainties – that is significantly different from the everyday world-picture, so that the latter may remain in the background while the player is immersed in the world-picture of the game. Lastly, I clarify why this immersion in a virtual world-picture is really achieved when the individual is able to develop narratives based on virtual certainties in order to address video game challenges.